Development and validation of a psychometric scale for assessing healthcare professionals' knowledge in radiation protection. Issue 2 (May 2019) - Schroderus-Salo, T.; Hirvonen, L.; Henner, A.; Ahonen, S.; Kääriäinen, M.; Miettunen, J.; Mikkonen, K.
Abstract: Introduction: Healthcare professionals must sufficiently understand ionising radiation and the associated protection measures to avoid unnecessarily exposing patients and staff to ionising radiation. Hence, a proper safety culture is important to lowering health risks. The development and establishment of an instrument that can indicate healthcare professionals' understanding/knowledge of radiation protection concepts can greatly contribute to a good safety culture. The purpose of the present study was to develop and psychometrically test the Healthcare Professional Knowledge of Radiation Protection (HPKRP) self-evaluation scale, which was designed to measure the knowledge level of radiation protection by healthcare professionals working with ionising radiation in a clinical environment. Methods: The presented research employed a cross-sectional study design. Data were collected from eight Finnish hospitals in 2017. A total of 252 eligible nurses responded to the newly developed HPKRP scale. The face and content validity were tested with the Content Validity Index (CVI). Explorative factor analysis was used to test construct validity, whereas reliability was tested with Cronbach's alpha. Results: Overall S-CVI for the HPKRP scale was 0.83. Exploratory factor analysis revealed a three-factor model for the HcPCRP scale containing 33 items. The first factor was defined by Radiation physics and principles of radiation usage, the second factor by Radiation protection, and the third factor by Guidelines of safe ionising radiation usage . These three factors explained 72% of the total variance. Cronbach's alpha coefficient for the scale ranged from 0.93 to 0.96. Conclusion: The results provide strong evidence for the validity and reliability of the HPKRP scale. Additionally, educators can use the scale to evaluate healthcare students' understanding in radiation safety before and after education. Highlights: There is a lack of validated instruments that measure radiation protection knowledge among healthcare professionals. The HPKRP scale was designed with a focus on safe radiation use in the clinical environment. This instrument can be used to measure healthcare professionals' knowledge in radiation protection. The instrument can be used to measure the effectiveness of radiation education..